Isolation of compounds from ethyl acetate crude extracts in stem bark of pithecellobium jiringa / Norshakireen Khairul Shahrom - Khairul Shahrom, Norshakireen (Faculty of Applied Sciences, 2016)
In this study, ethyl acetate (EA) crude extract of stem bark of Pithecellobium jiringa was subjected to fractional isolation and proceeds with antifungal activity determination. Five different EA fractions were successfully isolated and labelled as FI, F2, F3, F4, and F5. The isolation of EA crude was achieved by using column chromatography method and analysed by thin layer chromatographic technique. Few compounds were identified based on TLC result on TLC plate. However, the compounds give negative response to antifungal test, which means, the compounds in the five fractions were not active towards antifungal test on T. mentagrophyte and C. albicans. There is no inhibition activities reported towards on these two fungi. The compounds then were been characterized by using GCMS and IR spectrometer. The major compound is unsaturated fatty acid which is hexadecanoic acid methyl ester.